Donor-induced depoliticisation of development implementation: the case of Ghana's Compact I. Issue 3 (3rd April 2017) - Boateng, Oheneba A.
ABSTRACT: Based on empirical evidence from a donor-funded project in Ghana, this article demonstrates that when development implementation is depoliticised, targets will likely be achieved within budget and on time. Funded and supervised by the Millennium Challenge Corporation of the United States, Ghana Compact I has been recommended as a model for future development implementation. This article is an attempt to explain this success, compared to select social programmes. It argues that Compact I was implemented successfully because it was insulated from political interference, and suggests that donor-induced depoliticisation offers a route to successful development implementation in recipient countries.